Comparison of a 1-MHz and a 2-MHz probe for microembolus detection using transcranial Doppler ultrasound - Droste, Dirk W.; Lerner, Thomas; Dittrich, Ralf; Ritter, Martin; Ringelstein, E. Bernd (Neurological research (New York), 2005)
Objectives: Clinically silent microembolic signals (MES) can be detected by transcranial Doppler sonography (TCD). There is theoretical evidence that lower ultrasound emission frequencies may lead to a higher signal intensity and thus sensitivity to detect MES. We compared a 1-MHz probe with a 2-MHz probe regarding sensitivity in the detection of MES. Moreover, embolus detection by transcranial Doppler ultrasound is very time consuming and semi-automated detection is mandatory. Therefore, we studied an on-line algorithm using the bi-gate technique and the two transmission frequencies. Methods: After defining detection thresholds of ≥ 12 dB (1 MHz) and ≥ 10 dB (2 MHz) with eight normal subjects as MES-negative controls, taking into account natural fluctuations of the Doppler spectrum, we studied 36 patients with ischaemic events and five asymptomatic patients with incidental embolic sources. All patients subsequently underwent a 1-hour unilateral embolus detection from the middle cerebral artery (MCA) or the posterior cerebral artery (PCA), respectively, using 1 and 2 MHz for 30 minutes each in a randomized order. The software algorithm was compared with a blinded off-line analysis by an experienced observer as a gold standard. Results: The investigator detected 198 MES (range 0-41 MES) in the recordings of 29 patients out of the 41 patients using the 1-MHz probe and 101 MES (range 0-32 MES) in the recordings of 14 patients using the 2-MHz probe (p=0.0007). Sensitivity of the software to detect MES confirmed by the investigator was 31% using 1 MHz and 41% using 2 MHz. The positive predictive value was 6 and 30%, respectively. Discussion: The sensitivity and positive predictive values of the automated algorithm to detect MES were unacceptably low for clinical practice with both frequencies. The use of 1 MHz instead of 2 MHz may, however, be useful when evaluating the recordings off-line by an experienced blinded observer.